Adolescent girls in physical education and sport: An analysis of influences on participation - Whitty, J. M. (1999)
This study investigates the influences on participation in physical activity of thirty adolescent girls from a metropolitan secondary school in Victoria. It seeks to understand how they perceived, experienced and explained their involvement or non involvement in both competitive and non competitive physical activity during four years of their secondary schooling. Participants experienced physical education as both a single sex group in Years 7 and 9 and a coeducational group in Years 8 and 10. They were exposed to a predominantly competitive curriculum in Years 7 to 9 and a less structured, more social, recreational program in Year 10. These experiences enabled them to compare the differences between class structures and activity programs and identify the significant issues which impacted on their participation. Large Australian population studies have revealed that fewer girls participated in sport and regular physical activity than boys. An important consequence is that girls miss out on the health benefits associated with participating in physical activity. Other research has found adolescence is the time that girls drop out of competitive sport. However, an important issue is whether girls who drop out of competitive sport cease to be involved in any physical activity. There are some studies which have reported good participation rates by adolescent girls in non competitive, recreational forms of physical activity and the possibility exists that they may drop out of competitive and into non competitive physical activity. This study primarily utilises a qualitative approach in contrast to previous studies which have largely relied upon the use of surveys and questionnaires. Whilst quantitative research has provided useful information about the bigger picture, there are limitations caused by reliance on the researchers' own interpretations of the data. Additionally there is no opportunity for any clarification and explanation of findings and trends by the respondents themselves. The current study utilized qualitative individual and collective interviews in three stages. Questions were asked in the broad areas of coeducation and single sex classes, preferences for competitive or recreational activity and body image issues. Some quantitative information focusing on nature and extent of current activity patterns was also gathered in the first stage. Thirty Year 10 girls participated in individual first interviews. Nine selected girls then took part in the second (individual) and third (collective) interview stages. Results revealed three groups based on the nature of physical activity involvement: [1] competitive activity group, [2] social activity group and [3] transition group. The transition group represented those who were in the process of withdrawing from competitive sport to take up more non competitive, recreational activity. The most significant difference between groups was skill level. On the whole those entering adolescence with the highest skill levels, such as those in the competitive group, were the most confident and relished competing against others. The social group was low in skill and confidence and had predominantly negative experiences in physical education and sport because their deficiencies were plainly visible to all. Similarly, a lack of skill improvement relative to those of 'better performers' affected the interest and confidence levels of those in the transition group. Boys' domination in coeducational classes through verbal and physical intimidation of the less competent and confident girls and exclusion of very competent girls was a major issue. Social and transition group members demonstrated compliance with boys' power by hanging back and sitting out of competitive activities. Conversely, the competitive group resisted boy's attempts to dominate but had to work hard to demonstrate their athletic capabilities in order to do so. Body image issues such as the skimpy physical education and sport uniform along with body revealing activities such as swimming and gymnastics, heightened feelings of self-consciousness and embarrassment for most girls. When strategies were adopted by social and transition group members to avoid any body exposure or physical humiliation, participation levels were subsequently affected. However, where girls felt confident about their physical abilities and body image, they were able to ignore their unflattering uniforms and thus participation was unaffected. Specific teaching practices such as giving more attention to boys, for example by segregating the sexes in mixed classes to focus attention on boys, reinforced stereotypical notions of gender and contributed to the inequities for girls in physical education. The competitive group were frustrated with having to prove themselves as capable as boys in order to receive greater teacher attention. The transition group rejected teacher's attempts to coerce them into participating in the inter school sports program. The social group believed that teachers viewed and treated them less favourably than others because of their limited skills. Girls were not passive in the face of these obstacles. Rather than give up physical activity they disengaged from competitive sport and took up other forms of activity which they had the confidence to perform. These activity choices also reflected their expanding social interests such as spending time with male and female friends outside school and increased demands on their time by study and part time work commitments. This study not only highlighted the diversity and complexity of attitudes and behaviours of girls towards physical activity but also demonstrated that they display agency in making conscious, sensible decisions about their physical activity choices. Plain Language Summary of Thesis Adolescent girls in physical education and sport; An analysis of influences on participation by Julia Whitty Submitted for the degree of Master of Applied Science Deakin University Supervisor: Dr Judy Ann Jones This study investigates the influences on participation in physical activity of thirty adolescent girls from a metropolitan secondary school in Victoria in order to understand how girls' perceived, experienced and explained their involvement or non involvement in both competitive and non competitive physical activity. Qualitative individual and collective interviews were conducted. Questions focussed on attitudes about coeducation and single sex classes, preferences for competitive or recreational activity and feelings about body image. Some quantitative information about the nature and extent of current activity patterns was also gathered in the first stage. Thirty Year 10 girls participated in individual first interviews. Nine selected girls then took part in the second (individual) and third (collective) interview stages. Results revealed three clearly different groups based on the nature of physical activity involvement (1) Competitive, (2) Social and (3) Transition (those in the process of withdrawing from competitive sport to take up more non competitive, recreational activity). The major difference between groups was skill level. Those entering adolescence with the highest skill levels were more competent and confident in the coeducational and competitive sport setting. Other significant issues included boys' domination, body image and teaching behaviours and practices.